Optimasi Layanan Aplikasi Digital Pasca Pandemi Melalui Kolaborasi Organisasi Gojek-Tokopedia - Achmad Yudhistira Mutho’a; Muhammad Fais Zalfa Ramadhan; Muhammad Rif’an (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The COVID-19 pandemic has profoundly changed the business landscape, especially in the use of digital applications. During the pandemic period, digital applications have become the main means for individuals and organizations to stay connected, transact and carry out various activities. However, the pandemic has also exposed several weaknesses in digital application infrastructure and services, such as reduced performance and weaknesses in data security. In facing these challenges, inter-organizational collaboration becomes increasingly important. Such collaboration can help in establishing new industry standards and increase user confidence. On the other hand, innovation in digital application services is also key in meeting user needs after the pandemic. The impact of post-pandemic organizational changes also affects application usage patterns and demand for digital services. This research uses a quantitative survey method by collecting data through questionnaires to understand user attitudes and perceptions towards post-pandemic digital application services.